Colorectal cancer screening method based on excrement sample - LIU RUI (2021)
The invention discloses a method and a kit capable of accurately detecting colorectal cancer or colorectal cancer precancerous lesion adenoma as well as a related non-transient computer readable medium and a computer system. According to the scheme provided by the invention, the blood components, the gene mutation, the DNA methylation and the intestinal bacteria content in the excrement sample ofthe subject are comprehensively analyzed from at least four dimensions, so that early detection of the colorectal cancer, particularly accurate detection in the adenoma stage, is realized. 本申请公开了一种能够准确检测结直肠癌或结直肠癌前病变腺瘤的方法、试剂盒以及相关的非暂态计算机可读介质和计算机系统。本申请提供的方案通过从至少四个维度综合分析受试者的粪便样本中的血液成分、基因突变、DNA甲基化及肠道细菌含量，从而实现结直肠癌的早期检测，特别是在腺瘤阶段的准确检测。